WACANA PEREMPUAN ISLAM DALAM BERPOLITIK - Nurfuadi, Nurfuadi (Yinyang: Jurnal Studi Islam Gender dan Anak, 2008)
By Koran, Allah explained that there is nothing different between man and women, all of them have some potency in Allah’sview, except their iman and taqwa, and nothing different man and woman in Islam, included in politics because woman got same potencywith man. If we see Koran text, imprinted have tendency to woman’s problem more caused base of our understanding and interpretationthat wrong to that text, because boundary (marginalization) to woman’s right from a perception that is perception folk-etymology aboutwoman.